Diagnosis of lumbosacral intervertebral disc disease and protrusion in a horse using ultrasonographic evaluation and computed tomography. (24th December 2015) - Krueger, C. R.; Gold, J.; Barrett, M. F.; Aboellail, T. A.
Summary: This case report describes the clinical presentation, diagnostic imaging modalities, treatment and post mortem evaluation of lumbosacral intervertebral disc protrusion in a mature Quarter Horse gelding 10 days after initial signs were noted. Grade 3 hindlimb ataxia, conscious proprioceptive deficits, urinary and faecal incontinence were present, which did not improve with anti‐inflammatories, antimicrobial therapy, corticosteroids, antioxidant therapy, cold‐laser therapy or electroacupuncture. Imaging modalities utilised ante mortem were computed radiography, transcutaneous and transrectal ultrasonography. Transrectal ultrasonography yielded findings highly suggestive of lumbosacral intervertebral disc protrusion and due to the lack of improvement and a poor prognosis, the horse was humanely subjected to euthanasia. Post mortem computed tomography, necropsy and histopathological evaluation confirmed lumbosacral intervertebral disc disease and protrusion into the spinal canal with subsequent impingement of the spinal nerve roots. Lumbosacral intervertebral disc protrusion as a clinical disease in the horse has not been previously described and should be included as a differential diagnosis in cases with acute hindlimb ataxia, proprioceptive deficits, and urinary and faecal incontinence.